A matrix pencil to the blind source separation of artifacts in 2D NMR spectra - Stadlthanner, K. (2012)
Multidimensional proton nmr spectra of biomolecules dissolved in aqueous solutions are usually contaminated by an intense water artifact. We discuss the application of the generalized eigenvalue decomposition (GEVD) method using a matrix pencil to solve the blind source separation problem of removing the intense solvent peak and related artifacts. 2D NOESY spectra of simple solutes as well as dissolved proteins are studied.